Inferno : a novel - Brown, Dan, 1964- (New York : Doubleday, 2013)
Harvard professor of symbology Robert Langdon finds himself on the run in Florence and in possession of a series of codes, created by a brilliant scientist obsessed with Dante's classic poem "The Inferno," that may unlock a terrifying secret that could devastate life on earth.
Adult
Adult
Keywords: Langdon, Robert (Fictitious character) -- Fiction; Cryptographers -- Fiction; Dante Alighieri, -- 1265-1321. -- Fiction; Langdon, Robert (Fictional character) -- Fiction; Cryptographers -- Fiction; Dante Alighieri, -- 1265-1321. -- Fiction; Adventure fiction; Adventure fiction; Suspense fiction